To the Tashkent Station : Evacuation and Survival in the Soviet Union at War - Manley, Rebecca, 1973- (Book collections on Project MUSE., 2009)
Based on previously unexploited archival collections in Russia, Ukraine, and Uzbekistan, this book offers a novel look at a war that transformed the lives of several generations of Soviet citizens.